P624 Vedolizumab can induce clinical remission in patients with chronic antibiotic-refractory pouchitis: A retrospective single-centre experience. (16th January 2018) - Verstockt, B; Claeys, C; Van Assche, G; D'Hoore, A; Wolthuis, A; Vermeire, S; Ferrante, M
Abstract: Background: Chronic antibiotic-refractory pouchitis affects up to 15% of patients with ulcerative colitis (UC) following colectomy with ileal pouch-anal anastomosis (IPAA). Therapy with anti-TNF agents has demonstrated efficacy in retrospective series, whereas data on vedolizumab (VDZ) therapy are scarce. We here report efficacy data of VDZ in patients with chronic antibiotic-refractory pouchitis. Methods: We retrospectively assessed all records from UC patients who underwent IPAA and were exposed to VDZ thereafter in our tertiary referral centre. Patients enrolled in a placebo controlled phase IV program with VDZ were excluded, as well as patients with a baseline modified pouchitis disease activity index (mPDAI) < 5 or with Crohn's disease-related complications of the pouch. All patients received VDZ 300 mg IV at Weeks 0, 2, and 6, whereafter maintenance therapy q8 was continued. The primary endpoint, clinically relevant remission defined as a mPDAI <5 and a reduction of overall score ≥2 points from baseline, was assessed at Week 14. Results: Twelve patients were identified (median (interquartile range) mPDAI 8.0 (7–8) at baseline). All but two patients (83.3%) underwent colectomy because of refractory UC and two for high-grade dysplasia. All but one J-pouches were two-stage procedures, constructed 6.4 years (2.8–12.3) prior to inclusion. All patients developed chronic antibiotic-refractory pouchitis after a median of 1.5 years (0.9–7.8), for which they were previously treated with several courses of antibiotics (100%), thiopurines (16.7%), infliximab (50.0%), or adalimumab (33.3%). mPDAI decreased from 8 (7–8) at baseline to 3 (1.5–6) at Week 14 ( p = 0.016), resulting in a clinical relevant remission rate of 81.8%. Endoscopic PDAI sub-score dropped from 6 (5–6) to 3 (2–4, p = 0.03). Steroid free clinicalremission was observed in 63.6% of patients, and antibiotic free remission rate was 54.5% at Week 14. No differences in C-reactive protein, haemoglobin or albumin could be found between baseline and Week 14. After a median follow-up of 46 weeks (14.0–105.3), 63.6% of patients were still in clinical remission. Four (33.3%) patients stopped therapy because of primary non-response ( n = 2), loss-of response ( n = 1) or clinical and endoscopic remission ( n = 1). Two patients reported new onset of arthralgia and no other adverse events were reported. Conclusions: In this case series, VDZ was efficacious and safe to induce clinical remission in patients with chronic antibiotic-refractory pouchitis. Final confirmation is expected via an ongoing phase IV, placebo-controlled randomised controlled trial (NCT02790138).